2016
DOI: 10.1002/jnr.23965
|View full text |Cite
|
Sign up to set email alerts
|

Brain Diffusivity and Structural Changes in the R6/2 Mouse Model of Huntington Disease

Abstract: Diffusion-weighted magnetic resonance (DW-MR) is an important diagnostic tool in Huntington disease (HD), a fatal hereditary neurodegenerative disorder. To clarify the nature of diffusivity changes in HD, we compared the apparent diffusion coefficient of water (ADC ) acquired by DW-MR with extracellular space volume fraction α and tortuosity λ, measured by the iontophoretic method in the R6/2 mouse model of HD and in wild-type controls (WT). In anisotropic globus pallidus (GP), diffusion measurements were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…In the latter study, the authors presented parallel RTI data from the same animals that corroborated the increase in cortical ECS volume compared with controls. MRI has further been used to show an increase in α of the globus pallidus in experimental Huntington's disease, consistent with observed cell death in this nucleus (Vorisek et al, 2017; Figure 3). The cell death and increased ECS volume were interestingly not associated with changes in FIGURE 3 | In vivo mouse brain MRI images depicted as the apparent diffusion coefficient of water (ADC W ), as per the calibration bar.…”
Section: Magnetic Resonance Imagingsupporting
confidence: 67%
See 1 more Smart Citation
“…In the latter study, the authors presented parallel RTI data from the same animals that corroborated the increase in cortical ECS volume compared with controls. MRI has further been used to show an increase in α of the globus pallidus in experimental Huntington's disease, consistent with observed cell death in this nucleus (Vorisek et al, 2017; Figure 3). The cell death and increased ECS volume were interestingly not associated with changes in FIGURE 3 | In vivo mouse brain MRI images depicted as the apparent diffusion coefficient of water (ADC W ), as per the calibration bar.…”
Section: Magnetic Resonance Imagingsupporting
confidence: 67%
“…It is apparent that water diffusion in the ventricles is much higher than in denser parenchyma, as expected. From Vorisek et al (2017), with permission.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Several transgenic mouse models have been introduced to overcome this drawback of neurotoxic lesion models 31,33,34) . These models express genomic DNA or cDNAs encoding mutant HTT under the control of endogenous promoters and display many of the typical pathological features of early HD 9,16,24,28,30,35,36) .…”
Section: Discussionmentioning
confidence: 99%
“…A proper animal model for HD is essential to determine the exact mechanism of HD and to develop new therapeutic modalities, such as cell therapy. Thus, some investigators have developed animal models, including a drug-induced rat model using quinolinic acid and knock-in and transgenic mouse models [ 8 , 27 , 31 , 33 , 34 ]. In addition, in vivo genetic rat models induced by lentiviral-mediated expression of mutant HTT in the striatum have been introduced [ 6 , 20 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…After all, HD is an age-related disease, and in normal brain aging, changes to the cortex also occur (Gray, Shirasaki et al 2008, Nana, Kim et al 2014, Vorisek, Syka et al 2017. While some studies indicated a link between peroxisomes and Alzheimer's disease, it was also unclear if PEX5 levels were affected at all in the normal, aging brain (Kou, Kovacs et al 2011, Dorninger, Forss-Petter et al 2017, Islinger, Voelkl et al 2018.…”
mentioning
confidence: 99%